The Influence Of Business Interest And Social Media On Student Entrepreneurship - Tiara Clarissa Gunawan; Habiburrahman Habiburrahman (Cita konsultindo, 2024)
This research aims to find out and analyze the influence of business interest and social media on entrepreneurship in Management Study Program students at Bandar Lampung University. This research used a population of 168 Bandar Lampung University students, and the sample taken from this research was 25% of the 168 students so that 42 students were determined as the research sample, however, to make the research easier the researcher determined 50 students as research in order to get more answers. varies. In collecting data sources, researchers use primary data sources, namely questionnaires that will be distributed to respondents, then the results of the research will be tested using multiple linear analysis, coefficient of determination test, t test and F test. Based on the research results, business interest and social media are both partial and second ANOVA have a significant effect on entrepreneurship among Economics and Business Students class of 2020 at Bandar Lampung University.